The comparison of prints produced by CTP and conventional plate - (:unkn) unknown (My University, 2006)
CtP which was first introduced into the printing sector in Drupa Printing Fair in 2000 has recently started to be used intensively as its price was lowered and its physical appearence was minimised. In the last two years, nearly all of the big printing houses became extensive users of CtP. It is clear that the printing quality of the plates prepared by CtP is better than the plates prepared by ordinary films. As there are limited technical references, the sector is still faced with problems in the usage of CtP. In the present study, a photograph in a ISO 300 standart and a UGRA 82 plate control scale were posed together to form a film and CtP into the plates. A print was done into Exprint 300 g/m 2 cartonboard produced by Kartonsan cartonboard factory, the biggest producer in Europe with CMYK inks. It was tried not to change physical conditions during the preparation of the plate and the print. The tramtone values in the plate were passed unchanged. In addition, the optical and mechanical dot gain were measured on the plates. The quality of dots on the surface of the plates was viewed by an optical microscope. The mechanical dot gain, trapping and solid tone values were measured by a printing densitometer at the surface of the printed matter and these parameters were graphically evaluated.